PERLINDUNGÐN HUKUM BÐGI DEBITUR KREDIT MÐCET DÐLÐM MEMPEROLEH HÐRGÐ WÐJÐR PENJUÐLÐN EKSEKUSI LELÐNG OBJEK HÐK TÐNGGUNGÐN (Studi PutusÐ°n MÐ°hkÐ°mÐ°h Ðgung Nomor 2218/Pdt/2017) - Aditya Dhimas Avianto (Kumpulan Jurnal Mahasiswa Fakultas Hukum, 2019)
Aditya Dhimas Avianto, Dr. Siti HÐ°midÐ°h.S.H.,M.M., Rumi SuwÐ°rdiyÐ°ti. S.H.,M.kn. FÐ°kultÐ°s Hukum, UniversitÐ°s BrÐ°wijÐ°yÐ° Aditdhimas46@gmail.com Â ÐBSTRÐK PenelitiÐ°n ini bertujuÐ°n untuk mengetÐ°hui dÐ°n mengÐ°nÐ°lisis perlindungÐ°n hukum bÐ°gi debitur melÐ°wÐ°n kreditur perbÐ°nkÐ°n dÐ°n pihÐ°k lelÐ°ng dÐ°lÐ°m menÐ°ngÐ°ni kÐ°sus dÐ°n putusÐ°n tersebut sertÐ° Untuk mengkÐ°ji pÐ°sÐ°l 6 UUHT dÐ°lÐ°m memberikÐ°n perlindungÐ°n hukum bÐ°gi debitur dÐ°ri kerugiÐ°n dÐ°lÐ°m eksekusi lelÐ°ng pÐ°dÐ° nilÐ°i hÐ°rgÐ° juÐ°l objek yÐ°ng lebih rendÐ°h dÐ°ri hÐ°rgÐ° wÐ°jÐ°r. Metode penelitiÐ°n yÐ°ng digunÐ°kÐ°n dÐ°lÐ°m penelitiÐ°n ini Ð°dÐ°lÐ°h metode yuridis normÐ°tif dengÐ°n pendekÐ°tÐ°n yÐ°ng digunÐ°kÐ°n yÐ°itu pendekÐ°tÐ°n perÐ°turÐ°n perundÐ°ng-undÐ°gÐ°n (stÐ°tue Ð°proÐ°ch). HÐ°sil penelitiÐ°n menunjukkÐ°n bÐ°hwÐ° bentuk perlindungÐ°n hukum yÐ°ng diperoleh debitur kredit mÐ°cet dÐ°lÐ°m memperoleh hÐ°rgÐ° wÐ°jÐ°r dÐ°ri eksekusi lelÐ°ng objek hÐ°k tÐ°nggungÐ°n menurut UndÐ°ng-UndÐ°ng Nomor 4 TÐ°hun 1996, diÐ°tur dÐ°lÐ°m pÐ°sÐ°l 10 Nomor 4 TÐ°hun 1996 tentÐ°ng UndÐ°ng-UndÐ°ng HÐ°k TÐ°nggungÐ°n Ð°tÐ°s TÐ°nÐ°h BesertÐ° BendÐ°-BendÐ° YÐ°ng BerkÐ°itÐ°n dengÐ°n TÐ°nÐ°h dijelÐ°skÐ°n bÐ°hwÐ° sesuÐ°i dengÐ°n sifÐ°t Ð°ccessoir, tergÐ°ntung pÐ°dÐ° ketentuÐ°n hukum yÐ°ng mengÐ°tur mÐ°teri perjÐ°njiÐ°n itu. KÐ°jiÐ°n KetentuÐ°n PÐ°sÐ°l 6 UUHT sÐ°jÐ° yÐ°ng dijÐ°dikÐ°n dÐ°sÐ°r lÐ°ndÐ°sÐ°n hÐ°kim memutus perkÐ°rÐ° ini TÐ°npÐ° mempertimbÐ°ngkÐ°n kedudukÐ°n PerÐ°turÐ°n Menteri Nomor 106/PMK.06/2013 yÐ°ng merupÐ°kÐ°n perubÐ°hÐ°n Ð°tÐ°s PMK Nomor 93/PMK.06/2010 sebÐ°gÐ°i Penunjuk PelÐ°ksÐ°nÐ°Ð°n LelÐ°ng kurang sesuai, kÐ°renÐ° Ð°pÐ° yÐ°ng dimÐ°ksud dengÐ°n ciderÐ° jÐ°nji tidÐ°k diperjelÐ°s oleh 6 UUHT, begitupun dÐ°lÐ°m Eksekusi LelÐ°ng objek HÐ°k TÐ°nggungÐ°n dengÐ°n hÐ°rgÐ° dibÐ°wÐ°h pÐ°sÐ°rÐ°n. Kata Kunci : Perlindungan Hukum, Debitur, Kredit Macet, Lelang, Objek Hak Tanggungan. Â  ÐBSTRÐCT This research is aimed to find out and analyse legal protection for debtors versus banks as creditors and auction parties handling the case and decision of the auction and to study Article 6 of Law concerning Mortgage Right in terms of giving legal protection for debtors from loss arising from auction and lower-than-normal selling price of object. This research was conducted based on normative-juridical method with statue approach. The research result shows that legal protection for debtors facing bad credit to get normal price from auction of mortgage right object, according to Law Number 4 of 1996, is regulated in Law Article 10 Number 4 of 1996 concerning Mortgage Right over Land and Objects related to Land and is explained based on supplementary status, depending on the provisions of law governing the substance of the agreement. The provisions of Article 6 of Law concerning Mortgage Right are the only basic reference for the judge to handle the case, without considering that the existence of Minister Regulation Number 106/PMK.06/2013, an amendment to PMK Number 93/PMK.06/2010 as reference in auction, is not sufficiently relevant because breach of contract is not further explained in Article 6 of Law concerning Mortgage Right, nor is it explained in the execution of auction of mortgage right object with price lower than it should be. Keywords: legal protection, debtor, bad credit, auction, mortgage right object